A systematic review to determine the role of public space and urban design on sense of community (2023)
The aim of this research is to determine the effect that the physical characteristics of public spaces and their perceived quality have on residents’ sense of community (SoC). A sys tematic review was carried out following the protocol of the PRISMA guidelines; a systematic search was conducted in the Web of Science Core Collection, resulting in the retrieval of 637 records. After several screenings, 23 studies were identified. The results suggest that the perceived quality of public spaces exerts positive effects, but of moderate inten sity, on SoC (range = 0.13–0.4, Mβ = 0.24, SD = 0.1), as does the possibility of walking to public spaces within the neighbourhood (range = 0.02–0.57; Mβ = 0.22; SD = 0.21). The results indicate that designing public spaces that facilitate social interaction is the main factor for enhancing SoC. The main findings of this review justify the design of public spaces and built environments that favour interpersonal relationships between residents, serve as contexts for socialization and community participation and can be used to celebrate cultural and recreational events for promoting social capital in urban contexto